PENGAWETAN KAYU AGATHIS, BUNGUR, KARET, DAN TUSAM DENGAN METODE PENCELUPAN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This paper deals with a study on a momentary dipping of freshly sawn wood for short periods in a solution of 33% boric acid equivalent (BAE) and 33% BFCA preservative at ambient temperature, followed by one, two, three and four weeks of diffusion storage. Boron penetration were then calculated and analyzed. Results of the study reveal that timber species and preservatives do not any significant effect, but diffusion periods show highly significant effect to boron penetration. Boron penetration seemed is normally with the increas in diffusion storage period. Diffusion storage of four weeks for all timber tested in this experiment shows relatively good results, so that diffusion storage periods for four weeks may be recommended.